2019
DOI: 10.12968/bjom.2019.27.6.373
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of outpatient induction of labour

Abstract: Background Outpatient induction of labour is offered to relieve the pressure on inpatient stay and to improve women's experiences. Aim To contribute to the knowledge of outpatient induction of labour with the focus on women's experiences to inform practice. The question was: ‘What are women's experiences of outpatient induction of labour?’ Method A comprehensive literature review using a pluralistic approach and thematic analysis. Findings The review found three themes: the home as a positive setting for outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Regarding pregnant women's experience of outpatient induction, one study showed that being able to stay at home during part of the induction process was related to physical and emotional comfort and an improved childbirth experience 53 . Another indicated that the general experience with induction of labor was good but that women in the outpatient setting were more anxious, 34 while a third 36 found balloon ripening in the outpatient setting more desirable than prostaglandin and inpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pregnant women's experience of outpatient induction, one study showed that being able to stay at home during part of the induction process was related to physical and emotional comfort and an improved childbirth experience 53 . Another indicated that the general experience with induction of labor was good but that women in the outpatient setting were more anxious, 34 while a third 36 found balloon ripening in the outpatient setting more desirable than prostaglandin and inpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…As in the study by O'Brien et al 21 , women in our study were disappointed that they had not spontaneously gone into labor but had to be induced. However, being at home was described by the women as the next best thing to a spontaneous onset, because of the constant support from the partner, the familiarity of the home environment, the higher level of privacy, the freedom of movement and selfexpression, and their ability to carry on with their usual routines at home 3,7,11,13,21 . Despite that outpatient induction of labor gave women in our study a positive birth experience, women also described some aspects with the outpatient experience as less positive.…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis was conducted in collaboration by the first, second and last author to ensure the quality of the analysis 12 . We used the content analysis of Graneheim and Lundman 13 which included the following steps. In step 1, a thorough review of the entire text to form an overall impression.…”
Section: Methods For the Qualitative Data Analysismentioning
confidence: 99%